The Relationship of Sexual Activity in Menopausal Women With Quality of life - Sholihat, Suci (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2020)
Menopause is the cessation of menstrual cycles permanently to women who previously had menstruation every month, and not caused by pathological conditions. Sexuality is an important part in women’s life healthy and quality, changes experienced by menopausal women will lead to a crisis that affects the quality of life. This study was conducted to analyze the relationship of sexual activity in menopausal women with quality of life.This research conducted sectional method of sequential explanatory mixed method that collect and analyze quantitative data then followed by data collection and analyzing qualitative data based on quantitative result. The population was menopausal women in UPTD Yankes Kecamatan Soreang who matched with research criteria, i.e women who already menopause, married/had life spouse, having sex actively, not illiterate (can read and write). It used purposive sampling method, from  December 2017 to Januari 2018.      The result of sexual activity related to the quality of life of menopausal women. Age and education is related to the quality of life of menopausal women.The conclusions of this study were sexual activity in menopausal women related to quality of life. Social support, self-confidence and positive attitude towards the complaints of the menopause women, especially around sexuality in order to make a good quality of life.